(untitled) (Global Conference on Medical and Health Sciences, 2026)
Background: Sleep disorders, including insomnia, obstructive sleep apnea, and circadian rhythm disturbances, affect approximately 30–45% of the global adult population. Emerging evidence indicates that disrupted sleep profoundly alters the balance of key brain neurotransmitters — including serotonin, dopamine, gamma-aminobutyric acid (GABA), norepinephrine, acetylcholine, and orexin — with cascading consequences for mood, cognition, and systemic health. Objective: This study aimed to systematically evaluate the effects of sleep disorders on brain neurotransmitter homeostasis and to delineate the neurophysiological mechanisms linking sleep disruption to neurotransmitter dysregulation. Methods: A systematic review of 10 peer-reviewed studies published between 2013 and 2024 was conducted, encompassing neuroimaging, biochemical, polysomnographic, and clinical investigation data. Results: Sleep deprivation and chronic sleep disorders were associated with significant reductions in serotonin (−38%), dopamine receptor sensitivity (−29%), and GABAergic inhibitory tone, alongside elevations in norepinephrine and glutamate activity. Orexin system dysregulation emerged as a central mechanism linking sleep-wake instability to widespread neurotransmitter imbalance. Conclusion: Sleep disorders exert a profound and clinically significant impact on brain neurochemistry.